Humoral Immunity to Measles, Mumps, Rubella, Diphtheria, Tetanus and Pertussis After Cancer Treatment in Children - Sundell, Susanna; Laine, Miia; Järvelä, Liisa; Peltola, Ville; Vuorinen, Tytti; Lähteenmäki, Päivi; Schuez-Havupalo, Linnea (Wiley, 2025)
Background
Treatment for pediatric malignancies has distinct effects on the immune system.
Aims
Our aim was to measure humoral immunity to measles, mumps and rubella (MMR), and diphtheria, tetanus and acellular pertussis (DTaP) vaccines after pediatric cancer treatment.
Method
We assessed IgG titers of 52 children against the vaccine antigens post-treatment.
Results
After completed primary vaccination series for MMR and DTaP before treatment, post-treatment there was a considerable proportion of patients with below-reference titers against pertussis, diphtheria and tetanus, but only few subjects showed below-reference titers against measles, mumps and rubella. Our findings may have implications when considering re-vaccination policies.